(untitled) (Minerva, 2019)
In this paper, the scholar compares two hagiographic works belonging to VII century: Vita Desiderii (BHL 2148) of Sisebut and Passio Desiderii (BHL 2149) of an unknown Merovingian author. The scholar tries to prove that the Merovingian author knew Sisebut’s work from which he took some loans. The differences between these two works are explained by their different purposes.